Physiological levels of nitrate support anoxic growth by denitrification of Pseudomonas aeruginosa at growth rates reported in cystic fibrosis lungs and sputum - Line, Laura; Alhede, Morten; Kolpen, Mette; Kühl, Michael; Ciofu, Oana; Bjarnsholt, Thomas; Moser, Claus; Toyofuku, Masanori; Nomura, Nobuhiko; Høiby, Niels; Jensen, Peter Ø. (Frontiers in Microbiology, 2014)
Chronic Pseudomonas aeruginosa lung infection is the most severe complication in patients with cystic fibrosis (CF). The infection is characterised by the formation of biofilm surrounded by numerous polymorphonuclear leukocytes (PMNs) and strong O2 depletion in the endobronchial mucus. We have reported that O2 is mainly consumed by the activated PMNs, while O2 consumption by aerobic respiration is diminutive and nitrous oxide (N2O) is produced in infected CF sputum. This suggests that the reported growth rates of P. aeruginosa in lungs and sputum may result from anaerobic respiration using denitrification. The growth rate of P. aeruginosa achieved by denitrification at physiological levels ( 400 µM) of nitrate (NO3-) is however, not known. Therefore, we have measured growth rates of anoxic cultures of PAO1 and clinical isolates (n = 12) in LB media supplemented with NO3- and found a significant increase of growth when supplementing PAO1 and clinical isolates with ≥ 150 µM NO3- and 100 µM NO3-, respectively. An essential contribution to growth by denitrification was demonstrated by the inability to establish a significantly increased growth rate by a denitrification deficient ΔnirS-N mutant at <1 mM of NO3-. Activation of denitrification could be achieved by supplementation with as little as 62.5 µM of NO3- according to the significant production of N2O by the nitrous oxide reductase deficient ΔnosZ mutant. Studies of the promoter activity, gene transcripts and enzyme activity of the four N-oxide reductases in PAO1 (Nar, Nir, Nor, Nos) further verified the engagement of denitrification, showing a transient increase in their activation and expression and a rapid consumption of NO3- followed by a transient increase of NO2-. Growth rates obtained by denitrification in this study were comparable to our reported growth rates in the majority of P. aeruginosa cells in CF lungs and sputum. Thus, we have demonstrated that denitrification is required for P. aeruginosa growt